The Effect of Compensation and Work Discipline on Employee Performance in State Islamic Religious Higher Education - Akib, Akib; Mansyur, Mansyur; Kurdin, Kurdin; Demina, Demina (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze the effect of compensation and employee discipline on employee performance at IAIN Kendari. This study uses a quantitative approach. The research sample was 60 employees. Data analysis using descriptive and inferential analysis after fulfilling the requirements for normality, linearity, multicollinearity, and autocorrelation tests. Hypothesis testing using simple regression analysis and path analysis. The study results indicate that satisfactory compensation can lead to an increase in the performance of IAIN Kendari employees, and good work discipline can lead to an increase in the performance of IAIN Kendari employees. Fair compensation can lead to an increase in the performance of IAIN Kendari employees. This research implies that an increase in compensation can improve employee discipline and employee performance at IAIN Kendari.